2015
DOI: 10.1002/adma.201503319
|View full text |Cite
|
Sign up to set email alerts
|

Soft Graphene Nanofibers Designed for the Acceleration of Nerve Growth and Development

Abstract: Soft graphene nanofibers with recoverable electrical conductivity and excellent physicochemical stability are prepared by a controlled assembly technique. By using the soft graphene nanofibers for cellular electrical stimulation, the common inhibitory effect of long-term electrical stimulation on nerve growth and development is avoided, which usually happens with traditional 2D conductive materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
122
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 46 publications
1
122
0
Order By: Relevance
“…This rGO-modified electrode provided high H 2 O 2 sensitivity, low detection limits, and stronger electron transfer between tissue and electrode interfaces than traditional gold electrodes. Furthermore, Feng et al presented soft graphene-based nanofibers for detection of neuronal activity [132]. First, the negatively charged GO sheet was assembled on NH 3 plasma treated poly(vinyl chloride) nanofibers (called GO-NFs), and the GO-NFs were reduced to obtain the graphene nanofiber (G-NFs).…”
Section: Applications In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…This rGO-modified electrode provided high H 2 O 2 sensitivity, low detection limits, and stronger electron transfer between tissue and electrode interfaces than traditional gold electrodes. Furthermore, Feng et al presented soft graphene-based nanofibers for detection of neuronal activity [132]. First, the negatively charged GO sheet was assembled on NH 3 plasma treated poly(vinyl chloride) nanofibers (called GO-NFs), and the GO-NFs were reduced to obtain the graphene nanofiber (G-NFs).…”
Section: Applications In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…Although graphene-based materials have been widely utilized to fabricate films [131] or 3D scaffolds [132, 139], there is ongoing studies in order to extend the versatility and functionality of graphene and its chemical derivatives for neural regenerative medicine. 3D printing techniques might be a suitable method to fabricate the complex neural structure such as brain or neuronal conduit.…”
Section: Applications In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…As a new class of biomaterials, electrospun fibers have been widely explored and applied in tissue engineering, drug release, and biosensors, due to their inherent capability to mimic the hierarchical structure of the extracellular matrix (ECM). The large surface area, flexible surface functionality, and tunable morphologies further expand the applications of electrospun fibers in other fields . For example, as cell culture substrates, the microstructure of electrospun fibers can greatly influence the cellular growth behavior, such as morphologies, activity, proliferation, and differentiation .…”
Section: Introductionmentioning
confidence: 99%
“…The large surface area, flexible surface functionality, and tunable morphologies further expand the applications of electrospun fibers in other fields. [13][14][15][16][17][18][19] For example, as cell culture substrates, the microstructure of electrospun fibers can greatly influence the cellular growth behavior, such as morphologies, activity, proliferation, and differentiation. [20][21][22][23] Recent studies showed that the fibers in a uniaxial alignment and other well-organized architectures played a key role in providing topographical cues to direct and enhance cell growth.…”
mentioning
confidence: 99%